Peran Masjid dalam Meningkatkan Kesehatan Masyarakat melalui Pembinaan Spiritual, Sosial dan Fisik - Melisa Putri; Shafiah Shafiah; Hanna Sajiddah; Asyraf Hibatullah; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Mosques play an important role in the social life of Muslims, more than just a place of worship. In recent decades, mosques have begun to be seen as potential venues for carrying out a variety of activities that can support community well-being, one of which is in the area of health. The purpose of this article is to provide a more in-depth understanding of how places of worship, such as mosques, can play a significant role in improving the overall well-being and health of communities. involving qualitative methods. using several data collection methods that are qualitative in nature, including in-depth interviews, participatory observation, and documentation. In-depth interviews were conducted with mosque administrators, medical personnel, and worshipers to explore their understanding of various aspects of the health program implemented at the mosque. The interviews were semi-structured, where the researcher used flexible interview guidelines to allow informants to explain their experiences more freely. research results This article examines how mosques can function as health centers that not only provide medical services, but also play a role in health education and counseling to worshipers. The research includes an analysis of mosques that have run health programs, such as free health check-ups, counseling on healthy lifestyles, and raising awareness of the importance of health.